Stress enhanced intergranular corrosion of friction stir welded AA2024-T3. (April 2020) - Bocchi, Sara; Cabrini, Marina; D'Urso, Gianluca; Giardini, Claudio; Lorenzi, Sergio; Pastore, Tommaso
Highlights: AA2024 FSWed joints are not susceptible to stress corrosion cracking. More severe corrosion attack after intergranular tests is at the HAZ/TMAZ interface. Long term corrosion test evidenced a preferential attack in the zone of the nugget. The intergranular corrosion attack became penetrating in presence of loading. Abstract: The paper is aimed at the evaluation of intergranular corrosion of friction stir welded AA2024-T3 joints as a function of manufacturing parameters and loading conditions. Tests for intergranular corrosion assessment, long terms exposure tests, corrosion monitoring through electrochemical impedance spectroscopy and microstructural characterization of the corrosion morphologies were performed to evaluate the effect of loading on intergranular corrosion initiation and propagation. Electrochemical impedance spectroscopy spectra were collected during long term exposure tests to determine the onset of the attack and the propagation rate. A slight modification of the impedence modulus was observed during the exposure as a function of the process parameters. On the contrary, relevant effect of loading condition on intergranular corrosion initiation and propagation mechanisms was noticed. Although no stress corrosion cracking phenomena were evidenced, stress enhanced intergranular attack was observed on loaded specimens at the nugget, where coalescence of sub-micrometric and continuous copper-rich precipitates at the grain boundary occurred. These phenomena are mainly attributable to the thermo-mechanical action of the welding process. Intergranular attacks were not observed in the heat-affected zone and in the base metal, where grain recrystallization does not occur.